2003
DOI: 10.1097/01.gme.0000059861.93639.1a
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of serum phospholipid of premenopausal women and postmenopausal women receiving and not receiving hormone replacement therapy

Abstract: The results of this study indicate that the fatty acid composition of serum phospholipids in women is influenced by menopausal status and hormone use. These results are of interest because high levels of 20:3n-6 and low levels of docosapentaenoic acid have been associated with increased myocardial infarction plus stroke mortality from cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Together, this would confer a reduced risk of CVD in women. Stark et al previously reported that post-menopausal women had lower relative levels of serum palmitoleic acid compared to pre-menopausal and post-menopausal women receiving hormone therapy [34]. In contrast to Freedman et al [32], we did not observe sex differences in LDL-c and TAG levels.…”
Section: Sex Differences In Blood Lipids and Fatty Acidscontrasting
confidence: 95%
See 1 more Smart Citation
“…Together, this would confer a reduced risk of CVD in women. Stark et al previously reported that post-menopausal women had lower relative levels of serum palmitoleic acid compared to pre-menopausal and post-menopausal women receiving hormone therapy [34]. In contrast to Freedman et al [32], we did not observe sex differences in LDL-c and TAG levels.…”
Section: Sex Differences In Blood Lipids and Fatty Acidscontrasting
confidence: 95%
“…Together, this suggests that females have increased SCD activity compared to men. Stark et al previously reported that post-menopausal women had lower relative levels of serum palmitoleic acid compared to pre-menopausal and post-menopausal women receiving hormone therapy [34]. This suggests that the higher levels of palmitoleic acid and the SCD-16 desaturation index in young women may be related to hormone differences between the two sexes.…”
Section: Sex Differences In Blood Lipids and Fatty Acidsmentioning
confidence: 97%
“…However, mitochondrion also has higher levels of cardiolipin, which contains primarily 18:2n-6 and reportedly little to no DHA [31]. The significantly higher percentage of 18:0 in red gastrocnemius is also indicative of a higher proportion of phosphatidyl-ethanolamine in phospholipids [34]. The high percentage of 22:6n-3 observed in red gastrocnemius in the present study likely serves as structural cofactors to support fast oxidative activities [19].…”
Section: Discussionmentioning
confidence: 83%
“…Women of different hormonal status have different plasma phospholipid fatty acid profiles (59), and hormone replacement therapy has been associated with differences of EPA and DHA amounts in plasma phospholipids (60). Studies using fatty acid stable isotopes have reported that women of childbearing age have a greater potential to produce DHA than men (61,62).…”
Section: Discussionmentioning
confidence: 99%